Baltic Phytoremediation – soil remediation with plants. Issue 1 (October 2020) - Hogland, William; Katrantsiotis, Christos; Sachpazidou, Varvara
Abstract: The project Baltic Phytoremediation (BAPR), an implementing project of the Interreg South programme, aims to raise cross-border awareness about the availability of green phytoremediation technologies to remove environmental pollutants from soil or water, such as oil, industry-related contaminants, hazardous substances, heavy and toxic metals, nutrients and microplastics, through new arenas of cooperation that focus on circular economy approach. Contamination of land and soil increases and is a serious concern around the Baltic Sea region but further worldwide. The most common remedial technologies for related to the clean-up of soil is excavation, removal and disposal to a contained landfill. Therefore, heavily contaminated soils in landfills, can in some instances, mixing with another disposal of hazardous materials. In the Kalmar, a region of south-eastern Sweden, on the Baltic Sea, the glass waste dumps are removed in such old fashion way with no contribution towards the Circular Economy. The best available remediation strategy is soil washing strategy, an ex-situ technology with a chemical additive application to remove contaminants from the soil and wastewater. Recently, many studies have been carried out encouragingly the phytoremediation processes in different plant species. For instances, food crops, sunflower and Indian mustard are considered as the best plants for phytoremediation, as they have a role in phytoextraction of heavy metals. Phytoremediation research has gained the interest of the scientific society and governments over the last two decades, leading to the development of urban greening and ecology national parks. Orrefors park is one of the largest innovative urban site parks in Sweden with ecologically, socially and economically sustainable way with phytoremediation. The present project aims to explore the combination of phytoextraction with biomass generation and commercial utilization as an energy source, using the ash (bio-ore) that increase energy efficiency and reduce carbon emissions. The project includes pilot cases using innovative plant-based phytoremediation methods that cleaning of the contaminated soil.